The significance of incorporating the STEAM-center concept into the educational system of the Republic of Uzbekistan - Pulatova, Aziza (MMIT Proceedings, 2024)
In today's rapidly evolving technological landscape and globalized world, the STEAM (Science, Technology, Engineering, Art, and Mathematics) center concept has become an essential component of modern education. This article explores the significance of incorporating STEAM centers into the educational system in the Republic of Uzbekistan. The main benefits of STEAM education are discussed, including its interdisciplinary approach, development of critical and creative thinking skills, preparation for a digital economy, fostering teamwork, and strengthening the connection between theory and practice. These advantages emphasize the importance of STEAM for ensuring the sustainability and modernization of Uzbekistan's education system, enabling the country to effectively respond to current challenges and demands of the labor market.